Carta de Roberto H. Todd a J. J. Henna - Todd, Roberto H.; Henna, J. J. (My University, 1920)
Carta relacionada a honras fúnebres para Betances.
Keywords: Henna, J. J.--Correspondence.; Henna, J. J.--Correspondencia.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.; Coll y Toste, Cayetano, 1850-1930; Lastra, Charries; Benedicto Geigel, José E.